Proposed the New Product Concept Development in GRAN Company - Sekaryani, Nanda Nyayu; Ratnaningtyas, Sudrajati (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. Indonesia has the greatest number of UMKM amongst any other countries in the world, and still growing. The creative industry in its own or it self have the greatest potential compared to other business industry in Indonesia. Among all of 14 sectors in creative industry, fashion industry has contributed to the economy the most. GRAN. is a fashion company that creates bag for woman students for their daily activities. To survive in fashion industry that has grew rapidly in Indonesia, GRAN. company must to find the right new product development to find right product that suitable with the willingness of the customer. For that, GRAN. company will do New Product Development Process by Pearson. So the company can meet customer’s expectation from products that GRAN. company make. This research do New Product Development Process by Pearson, only done until step 3, which Concept Development and Testing. For the next step until done will be presented in the implementation plan. The research will take place in Bandung with giving the respondents questionnaire with semi-close question to woman students in Bandung with age 18 until 23 years old. The questionnaire spread only to the customers who have bought GRAN.’s product to know what aspect to be improve in the products. And from the research know the attributes that must be fulfilled by GRAN, company to meet their customer’s expectation. Data were analyzed by descriptive quantitative and qualitative in order to obtain good research results.Keywords: Fashion Industry, New Product Development, Customer Buying Decision, Concept Development and Testing, GRAN.